Impact of Multilingual Use on Speech Development of Children Aged 4-5 Years in TK TA 03 Pengkol - Khadiva, Liliana Nur; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The use of more than one language in everyday life is common in many families around the world. Children are often exposed to more than one language from an early age. Multilingualism, also called bilingualism, refers to a person's ability to communicate in two or more languages. This study aims to analyze the impact of multilingual use on speech development in children aged 4-5 years. Researchers will explore the positive or negative impacts, as well as factors that can moderate the results. The method used in this study is qualitative. The type of research used is a case study. The results of this study show that the use of multilingual (Indonesian, Javanese, and English) in the daily lives of children aged 4-5 years has both positive and negative impacts. The positive impacts include improving cognitive abilities and social skills, as well as readiness to face the times. However, some children experience confusion and speech delays. Significant supporting factors are a supportive school environment with structured and interactive teaching methods, as well as the consistent role of parents in language habituation at home. The influence of social media also motivates parents to teach foreign languages, especially English. Therefore, the right approach and support from the school environment and parents is essential in optimizing the benefits of multilingualism for children's language development.